Nanoliposome-encapsulated MAGE peptides: A promising melanoma vaccine to activate human dendritic cells - Azin Bavafa; Niloufar Salimian; Zeina Khazaei Koohpar; Amir Gholamzad; Hossein Fahimi; Maliheh Entezari; Ali Jebali; Najma Farahani; Mehrdad Hashemi (Results in Chemistry)
Background: Melanoma immunotherapy with MAGE-A/B-targeted vaccines faces challenges in achieving robust clinical responses. This study aimed to develop and evaluate a nanoliposome-encapsulated melanoma vaccine delivering MAGE-A and MAGE-B antigenic peptides to stimulate human dendritic cells (DCs). Methods: MAGE-A and MAGE-B peptide sequences were selected based on bioinformatics analysis. Nanoliposomes encapsulating these peptides were synthesized and characterized, and their ability to stimulate interleukin (IL)-1 and IL-2 expression in human DCs in vitro was assessed. Results: The synthesized nanoliposomes were spherical, averaged 110 nm in diameter, and efficiently encapsulated approximately 90 % of the peptides. In vitro experiments showed that exposure of DCs to the nanoliposomes resulted in increased IL-1 and IL-2 gene expression, with a maximum effect at a concentration of 240 μg/mL after 48 h. Conclusion: Nanoliposome encapsulation of MAGE-A/B peptides effectively delivers antigen to DCs and stimulates cytokine production in vitro. This nanoliposome-based vaccine shows promise as a potential melanoma immunotherapy strategy and warrants further in vivo investigation.